Temporomandibular joint involvement in ankylosing spondylitis - Arora, Pallak (BMJ Publishing Group, 2013)
Frequency of temporomandibular joint (TMJ) involvement in patients with ankylosing spondylitis (AS) has varied from 4% to 35%. It is more common in men and produces generalised stiffness in involved joints. Clinician should be suspicious of AS when a patient reports with painful restricted movements of joint, neck or back and with no trauma history. Conventional radiographic methods have allowed the demonstration of TMJ abnormalities in patients with AS, but CT is necessary to establish joint space relations and bony morphology. We describe a case of severe AS with TMJ involvement in a 40-year-old female patient and demonstrated TMJ changes on CT. A CT was able to demonstrate articular cartilage changes, disc- and joint abnormalities. Thus, if conventional radiographs in a symptomatic patient with rheumatic diseases are unable to demonstrate changes, CT can provide valuable additional information of the changes in the TMJ.